2023
DOI: 10.3390/su15032522
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Geopolitical Risk on International Direct Investment and Its Countermeasures

Abstract: Recent years have seen frequent geopolitical conflicts and the world economy has fallen into a recession. In order to explore how wars, terrorist attacks and international tensions affect foreign direct investment (FDI), this paper uses the fixed-effect model to investigate the impact of geopolitical risks on FDI flows in 41 countries during 2003–2020 from the perspective of market seeking, natural resource seeking and strategic resource seeking. The results show that, on the whole, geopolitical risks can sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In other words, increasing GPR deters FDI inflows. This evidence is consistent with the previous empirical findings of Ramcharran (1999), DesBordes (2010), Hayakawa et al (2013), Weiling and Martek (2021), Nguyen et al (2022), Thakkar and Ayub (2022), Bussy andZheng (2023), andYu andWang (2023). The implication of this finding is that in the context of transition economies, GPR could result in potential economic costs for MNCs.…”
Section: Discussion Of the Resultssupporting
confidence: 92%
“…In other words, increasing GPR deters FDI inflows. This evidence is consistent with the previous empirical findings of Ramcharran (1999), DesBordes (2010), Hayakawa et al (2013), Weiling and Martek (2021), Nguyen et al (2022), Thakkar and Ayub (2022), Bussy andZheng (2023), andYu andWang (2023). The implication of this finding is that in the context of transition economies, GPR could result in potential economic costs for MNCs.…”
Section: Discussion Of the Resultssupporting
confidence: 92%
“…In terms of the results of the studies, there was a negative correlation between FDI and geopolitical risk in general, while De Angelo et al ( 2010), Rauf et al (2016), Zeng and Li (2019), Asaad et al (2020), Afşar et al (2021), Ayten (2021), Caldara and Iacoviello (2022), Carpenter (2022), Özşahin et al (2022) are studies conducted on a single country. Artciles with a large number of cross-section units, such as many countries or companies, are reported by Chanegriha et al (2017), Dissanayakea et al (2018, Arslan (2019), Dedeoğlu et al (2019), Kim et al (2019), Wang et al (2019), Fania et al (2020, Le and Tran (2021), Luo (2021), Ceyhan and Gulcan (2022), Dastan et al (2022), Li et al (2022), Lu andLiu (2022), Nhuyen et al (2022), Thakkar and Ayub (2022), Busy and Zheng (2023), Feng et al (2023), Yu and Wang (2023). The selected literature summary from these studies is given below:…”
Section: Literature Reviewmentioning
confidence: 99%
“…Feng et al (2023) determined that GMM and geopolitical risks significantly reduced FDI inflows in 45 countries during the period 2005-2019. Yu and Wang (2023) examined the impacts of geopolitical risks on FDI flows in 41 countries between 2003 and 2020, considering market, strategic, and natural resources with the Fixed Effects Model. The test results showed that geopolitical risk could significantly impede FDI flows and this impact would differ according to development levels.…”
Section: Nhuyen Et Al (mentioning
confidence: 99%
“…A large body of literature examines the consequences of geopolitical risk in terms of macroeconomic factors such as economic growth [15,16], international direct investment [17], joblessness rates [18], inflation [19,20], and financial markets [21,22]. A good number of modern researchers have called attention to the impact of the geopolitical risk index on the cost of energy and metals [23][24][25][26].…”
Section: Literature Reviewmentioning
confidence: 99%